Respek vir die lewe en die doodstraf volgens die perspektief van Genesis 9:5-6 - P. Verster (Acta Theologica)
There are different views on the application of Genesis 9:5-6 in the debate on the value of life and the death penalty. In postmodern society it is considered inhumane to execute persons who committed murder. In this article different views are discussed and it is suggested that, according to Genesis 9:5, respect for life is absolute and that, although the death penalty is not explicitly mentioned, it provides an argument for upholding respect for life.